Decision making process in keystroke dynamics - Yaacob, Mohd Noorulfakhri; Syed Idrus, Syed Zulkarnain; Wan Ali, Wan Nor Ashiqin; Mustafa, Wan Azani; Jamlos, Mohd Aminudin; Abd Wahab, Mohd Helmy (IOP Publishing, 2020)
Computer system intrusion often happens nowadays. Various methods have been introduced to reduce and prevent these intrusions, however no method was 100% proven to be effective. Therefore, to improve the computer’s security, this writing will explain the application of KD in the application system. The effectiveness of KD could not guarantee one hundred percent to prevent the computer intrusion, but it can be used as a second level of security after the login page in the application system. The pattern and time taken while typing by an individual is the core for the second level of security check after the login page. This writing will elaborate and conclude past studies related to KD on the aspects of decisionmaking process. Various methods of processing KD data that have been used are listed and the results of the study are compared. The results of this writing are expected to help new researchers in the process of evaluating KD data.